The Effect of the Let’s Read Application and Interactive Flipbook as Digital Literacy Media on Students’ Reading Motivation - Sa'adah, Lailatus; Anjarwati, Rosi; Mindaudah, Mindaudah; Lailina, Hidayatul (Department of English Language Education, UIN Sunan Ampel Surabaya, 2026)
Reading motivation plays a crucial role in fostering students’ engagement and achievement in reading activities. With the increasing integration of digital technologies in education, various digital literacy media, such as reading applications and interactive e-books, have been introduced to support students’ reading experiences. This study aimed to investigate the effect of using the Let’s Read application and interactive flipbooks as digital literacy media on students’ reading motivation in English reading classes. A quasi-experimental posttest-only design was employed involving 100 tenth-grade students. The participants were divided into three groups: a Let’s Read group (n = 34), an interactive flipbook group (n = 31), and a printed book group (n = 35). Data were collected using a reading motivation questionnaire and analyzed through descriptive statistics, normality and homogeneity tests, and one-way analysis of variance (ANOVA). The findings revealed that the Let’s Read group obtained the highest mean score (M = 58.26, SD = 5.50), followed by the interactive flipbook group (M = 57.97, SD = 5.23) and the printed book group (M = 57.06, SD = 6.15). However, the ANOVA results indicated no statistically significant difference in reading motivation among the three groups, F(2, 97) = 0.427, p = .654. These findings suggest that although digital literacy media offer interactive and engaging reading experiences, they did not significantly outperform printed books in enhancing students’ reading motivation. The study highlights that factors beyond the reading medium itself may play a more important role in shaping students’ motivation to read.